Gastric outlet obstruction: an unusual case of primary duodenal tuberculosis - Kalpande, Sanket (BMJ Case Rep, 2017)
BACKGROUND: Tuberculosis is a major health problem worldwide. Gastrointestinal tuberculosis presenting as isolated involvement of the duodenum is a rare case. CASE PRESENTATION: A 13 year male, presented with features of gastric outlet obstruction. CT enterography scan showed circumferential mural thickening in first and second part of duodenal junction causing luminal narrowing. Upper GI endoscopy confirmed the narrowing of D1-D2 junction. Duodenal biopsy showed duodenitis with negative result for AFB stain, Helicobacter Pylori. Patient underwent roux-en-y gastro-jejunostomy. Histo-pathological findings were consistent with tuberculosis. Patient was started on AKT and discharged. At 3 months follow up; patient asymptomatic. CONCLUSION: The unusual location of gastrointestinal tuberculosis, lack of specific signs and symptoms, radiological studies and endoscopy findings makes diagnosis a challenge. The treatment of duodenal tuberculosis is still medical and surgery should be reserved for emergency like gastric outlet obstruction causing nutritional compromise.